Microglial dynamics and neuroinflammation in prodromal and early Parkinson’s disease - Frida Lind-Holm Mogensen; Philip Seibler; Anne Grünewald; Alessandro Michelucci (Journal of Neuroinflammation)
Abstract Parkinson’s disease (PD) is characterized by a drastic loss of dopaminergic neurons already at diagnosis. As this loss of neurons starts decades before diagnosis, understanding the prodromal stages of the disease might offer novel strategies to curb its progression. While the precise pathogenic mechanisms underlying PD remain incompletely understood, growing evidence suggests that neuroinflammation and immune dysregulation play a central role in the development and progression of the disease. Here, we delve into the emerging roles of microglia, the resident immune cells of the central nervous system, in the pathogenesis of prodromal and early-stage PD. We emphasize that microglia contribute to neuroinflammation, protein aggregation and neurodegeneration, although the underlying mechanisms are not yet known. Neuroimaging studies have provided valuable insights into the patterns of microglial activation detected in individuals with prodromal PD and at the time of clinical diagnosis. Furthermore, we highlight the complex interplay between immune dysregulation and neurodegeneration along PD development, including alterations in the peripheral immune system, brain-gut interactions and brain-immune interfaces. Lastly, we outline existing models for investigating microglial involvement in prodromal PD, along with the impact of anti-inflammatory therapies and strategies to modify risk factors. In conclusion, targeting microglial activation and immune dysfunctions in individuals at risk of PD could represent a promising preventive measure and may offer novel therapeutic strategies for early intervention and disease modification.